Joint preserved reconstruction after curettage in giant cell tumor of bone arising in the distal radius: Case report. (2015) - Sakamoto, Akio
Highlights: Giant cell tumor of bone is a locally aggressive tumor. Preserved joint reconstruction for tumors in the distal radius is challenging. To preserve the joint, we developed a new reconstruction technique using β-tricalcium phosphate (TCP) with strong compressive resistance. Function remains excellent, without any complications. Abstract: Introduction: Giant cell tumor of bone is a locally aggressive tumor. Preserved joint reconstruction for tumors in the distal radius is challenging, especially when there is extraosseous extension and less subarticular bone. Presentation of case: To preserve the joint, we developed a new reconstruction technique using β-tricalcium phosphate (TCP) with strong compressive resistance. Discussion and conclusion: Giant cell tumor of bone in the distal radius was treated by curettage and bone grafting, plus the use of β-TCP. This new method will preserve joint junction.